2016
DOI: 10.1080/03009742.2016.1190984
|View full text |Cite
|
Sign up to set email alerts
|

Large vessel involvement in biopsy-proven giant cell arteritis: incidence, distribution, and predictors

Abstract: The estimated incidence of LVI, detected by imaging in a clinical setting, was higher among patients with GCA than the reference population. The aorta was the most commonly affected vascular territory. The negative association with giant cells may suggest particular mechanisms in this subset of GCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 34 publications
1
7
1
2
Order By: Relevance
“…ESR and CRP are typically elevated in GCA, and it is highly infrequent (<3%) that both are normal 36 37. While several other serological biomarkers have been evaluated, none is sufficiently sensitive and specific for detection and assessment of disease activity or prediction of prognosis to recommend its use in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…ESR and CRP are typically elevated in GCA, and it is highly infrequent (<3%) that both are normal 36 37. While several other serological biomarkers have been evaluated, none is sufficiently sensitive and specific for detection and assessment of disease activity or prediction of prognosis to recommend its use in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of the association between the presence of giant cells and different clinical manifestations have generated con icting results. We have previously investigated the predictive value of different histopathologic features of TAB for LVI, and found a negative association with the presence of giant cells in the histopathological reports [22]. To our knowledge, this was the rst study to examine this relationship in patients with biopsy-proven GCA.…”
Section: Introductionmentioning
confidence: 87%
“…Patients with positive TABs performed between 1997 and 2010 who were diagnosed with GCA (N = 840) were identi ed, as previously described [39]. Among these, patients from two de ned areas of the county that had previously been included in two clinical studies [22,40] were pooled for the present analysis ( Fig. 1).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study comparing patients with GCA and TA concluded that despite similar distribution of vascular lesions, the angiographic picture of a short segment, tight stenosis of the subclavian artery in TA, as opposed to a long, tapering stenosis in GCA, may help distinguish such patients . Whereas large vessel involvement in GCA is recognized in about 15% of patients, large vessel dilatation is less recognized. A recent study compared patients with GCA with subclavian artery stenosis and subclavian artery dilatation in GCA, and found that those with LV dilation were more likely male, smokers, with associated coronary artery disease, and had a greater propensity to develop aortic aneurysms …”
Section: Giant Cell Arteritismentioning
confidence: 99%